NORMS OF TEACHER-STUDENT RELATIONSHIP TO PREVENT CONFLICT - Jamoldinova Sayyora Nodirbek kizi (Galaxy International Interdisciplinary Research Journal, 2021)
This article argues that norms and standards in the relationship between students and teachers are an important requirement of today, and it is this aspect that prevents them from entering into mutual conflict.